Penerapan Metode Games Based Learning Untuk Meningkatkan Minat Belajar Pada Siswa Kelas IV SD - Khaerunnisa Khaerunnisa; Latri Latri; Lestari Lestari; Hasan Hasan (Universitas Negeri Makassar, 2022)
This research is a Classroom Action Research with the aim of knowing the application of games based learning methods and to increase learning interest in fourth grade students of SD Telkom Makassar. The focus of this research is the application of games based learning method to increase students' interest in learning. The subjects of this study were the fourth grade students of SD Telkom Makassar, totaling 13 people in the even semester of the 2021/2022 academic year. Data collection techniques used in this study are questionnaires, observation sheets and documentation. The results showed that in the first cycle the teacher's teaching activities were in the good category and in the second cycle had increased to a very good category. In line with this, the fourth grade students' interest in learning also increased, in the first cycle it was in the good category and in the second cycle it increased to very good. From the results, it can be concluded that the application of games based learning methods to increase interest in learning in fourth grade students at SD Telkom Makassar has been successful.